COVID-19 associated with extensive pulmonary arterial, intracardiac and peripheral arterial thrombosis. Issue 8 (3rd August 2020) - Ferguson, Katie; Quail, Nathaniel; Kewin, Peter; Blyth, Kevin G
Abstract : We describe a patient with COVID-19 who developed simultaneous pulmonary, intracardiac and peripheral arterial thrombosis. A 58-year-old man, without major comorbidity, was admitted with a 14-day history of breathlessness. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection was confirmed by laboratory testing. Initial imaging revealed COVID-19 pneumonia but no pulmonary thromboembolism (PTE) on CT pulmonary angiography (CTPA). The patient subsequently developed respiratory failure and left foot ischaemia associated with a rising D-dimer. Repeat CTPA and lower limb CT angiography revealed simultaneous bilateral PTE, biventricular cardiac thrombi and bilateral lower limb arterial occlusions. This case highlights a broad range of vascular sequalae associated with COVID-19 and the fact that these can occur despite a combination of prophylactic and treatment dose anticoagulation.